Duchenne Muscular Dystrophy: An Overview of Diagnosis, Management, and Pharmacological Treatment - Alshammari, Mohammed Raghilan; Alshammari, Fahad Hamoud; Alshammri, Waad Hamoud; Alsirhani, Bashayr Basheer; Alanazi, Ahlam Juwaybir; Al-Doukhi, Muneerah Suliman; Altamimi, Eman Fahad; Safi, Noura Hassan Mohammed; Faraj, Amal Saleh; Alshammary , Wedad Mohammed; Al-Matrafi, Nouf Akash; Qaem, Alanazi Sulaiman (Journal of Ecohumanism, 2024)
Background: Duchenne muscular dystrophy (DMD) is a severe inherited neuromuscular disorder, primarily affecting males, characterized by progressive muscle weakness due to mutations in the dystrophin gene. This gene encodes dystrophin, a protein crucial for maintaining muscle cell integrity. DMD leads to the progressive loss of muscle function, cardiac complications, and intellectual disability. The disease typically results in wheelchair dependence by the early teens and early mortality due to respiratory or cardiac complications in the twenties. Aim: This overview aims to examine the diagnosis, management strategies, and pharmacological treatments for Duchenne muscular dystrophy. Methods: The article reviews current literature on the genetic basis, epidemiology, pathophysiology, and clinical manifestations of DMD. It also explores diagnostic methods including serum biomarkers, genetic testing, and muscle biopsy, as well as treatment options, particularly glucocorticoid therapy, and ongoing pharmacological interventions. Results: Early detection of elevated serum creatine kinase (CK) levels, along with genetic testing, is key to confirming DMD. Current pharmacological treatments primarily focus on corticosteroids to slow muscle degeneration, and new investigational therapies are exploring gene editing and protein restoration. Additionally, cardiomyopathy, a major complication, requires regular monitoring and management. Conclusion: Duchenne muscular dystrophy remains a challenging condition with significant impact on patients and their families. Early diagnosis and intervention are essential for improving outcomes, while ongoing research offers hope for more effective therapies. Effective management includes a multidisciplinary approach focusing on pharmacological, physical, and cardiac care.